Pengembangan Media Pembelajaran Berbasis Web pada Muatan PKn Tema 6 Subtema 1 Pembelajaran 1 Kelas V SD - Abdilla Putri Asri; Arda Purnama Putra; Putri Mahanani; Abdilla Putri Asri; Arda Purnama Putra (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2022)
Abstract: This experiment aims to realize the application of web intermediary tools in subjects of Civics Theme 6 Subtheme 1 Learning 1 which are valid according to media experts, material experts, practical according to users (teachers) and interesting according to users (students). The research was carried out in February-March at the Laboratory Elementary School, State University of Malang, class V. This experimental and improvement model utilizes the ADDIE (Analysis, Design, Development, Implementation, Evaluation) steps. The research instruments used were interviews, observations, and questionnaires. Analysis of the materials used in the experiment and improvement of this media, namely, quantitative fact analysis and qualitative fact analysis. The validity test was carried out with validators who were good at media, good at material, consumers to understand the effectiveness of media products according to users (teachers) and to find out the attractiveness of products according to users (students) totaling 31 people. The results of data analysis prove that media products get a value of 95 percent on the validity test by media experts, and get a score of 89 percent on the validity test by material experts. In the practicality test the product gets a value of 96 percent and small-scale trials get a score of 87 percent while large-scale trials get a value of 90 percent. Based on the results after being explained, it was concluded that the advanced intermediary products had correct, practical, and interesting categories to be used during Civics learning activities theme 6 sub-theme 1 learning 1 class V. Abstrak: Percobaan ini bertujuan agar mewujudkan penerapan alat perantara web pada mata pelajaran Pkn Tema 6 Subtema 1 Pembelajaran 1 yang valid menurut ahli media, ahli materi, praktis menurut pengguna (guru) dan menarik menurut pengguna (siswa). Penelitian mewujudkan turut bulan Februari-Maret di SD Laboratorium Universitas Negeri Malang kelas V. Model percobaan dan peningkatan ini memanfaatkan langkah-langkah ADDIE (Analysis, Design, Development, Implementation, Evaluation). Instrumen penelitian yang digunakan yaitu wawancara, observasi, dan angket. Analisis bahan yang dipakai dalam percobaan dan peningkatan media ini yakni, analisis fakta kuantitatif dan analisis fakta kualitatif. Uji validitas dilakukan dengan validator pandai media, pandai materi, konsumen bagi memahami efektif produk media menurut pengguna (guru) serta untuk mengetahui kemenarikan produk menurut pengguna (siswa) yang berjumlah 31 orang. Hasil analisis data membuktikan produk media mendapatkan nilai 95 persen pada uji validitas oleh ahli media, dan mendapatkan nilai 89 persen pada uji validitas oleh ahli materi. Pada uji kepraktisan produk mendapatkan nilai 96 persen serta uji coba skala kecil mendapatkan nilai 87 persen sedangkan uji coba skala besar mendapatkan nilai 90 persen. Berdasarkan dari hasil usai dijelaskan, peroleh kesimpulan maka produk perantara yang memajukan memiliki kategori valid, praktis, dan menarik untuk digunakan saat kegiatan pembelajaran muatan PKn tema 6 subtema 1 pembelajaran 1 kelas V.